Strategic Profitability: Extending the Resource-Based View for Hotel Businesses - Iriani, Nisma; Djaya, Andi Amrullah; Rostini, Rostini; Nurmillah, Nurmillah; Charatwattananich, Monparath (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
The strategic achievement of firms, even especially hotel industry is monopolized by the quantitative measures in financial reports. This study advances the neglected conversation of strategic profitability by the perspective hotel managers in recorded responses. They fill the questionnaires regarding the service-based resources, the strategic entrepreneurship capacity in established business, and finally the strategic profitability. 329 managers provide responses by the 5-point Likert scale, and the data serves as the basis for partial-least-square structural-equation modelling (PLS-SEM). The findings indicate the acceptance of all relationships as service-based resources are critical to build the strategic entrepreneurship, and measurable performance. The mediation test is also supported. This study establishes the critical importance of building a specific strategic measure for service firms, with which policy is catered.